Professionalization of VET teachers and Curriculum Development in VET System : Results of Survey, Practice and Challenges in Burkina Faso, Senegal and Germany - Sawadogo, Wendkouni J. Eric [Verfasser] (My University, 2017)
"VET systems in African countries do not match the qualifications and competences required in the labour market. Instead they are more theoretical focusing on the shrinking formal sector that offers very limited employment opportunities. Consequently, this leads to high unemployment of their graduates. Due to lack of alternative employment in the formal sector, a critical mass of these graduates is obliged to find occupations in the "informal sector". However they haven't been equipped with the requisite skills. A paradigm shift to the so-called "informal sector" must be done, so that local education and employment possibilities could be better taken into account in the policies of VET system, especially in the process of professionalization of teachers. In this process, the development of curricula for teachers and skilled workers becomes a key factor. Indeed, "the competence of skilled workers, i.e. their professionalism, in the "informal sector" esp. consists in the successful completion of professional work and business processes and their ability to secure fair financial remuneration for their services". In light of this, this paper shows how contextualized concepts and an Internship Reports-Based Method of Updating or Developing Curricula could contribute to Further Education of VET teachers." (author's abstract; BIBB-Doku)
Keywords: S System beruflicher Bildung; P 3.2 Lehrpersonal; L 1.3 Curriculumentwicklung; I 2.3.1 Afrika; Berufsbildungssystem; Bildungspersonal; Professionalisierung; Curriculumentwicklung; Burkina Faso; Senegal